2002
DOI: 10.1046/j.0014-2956.2001.02689.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally constrained human calcitonin (hCt) analogues reveal a critical role of sequence 17–21 for the oligomerization state and bioactivity of hCt

Abstract: Calcitonin (Ct) is a 32-residue peptide hormone that is mainly known for its hypocalcemic effect and the inhibition of bone resorption. Our previous studies have led to ]hCt (4), corresponding partial sequence peptides containing the lactam-bridged region 16-22, and nonbridged control peptides. Only 1 showed a higher Ct receptor binding affinity than hCt, whereas analogues 2-4 had similar receptor affinities to hCt.In the in vivo hypocalcemic assay, 3 and 4 were as potent as 1, whereas 2 completely lost the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 64 publications
0
52
0
Order By: Relevance
“…To test the ability to predict the effect of multiple amino acid substitutions on the aggregation rate of a polypeptide sequence, a series of short peptides were designed by using amino acids 10-21 of hCT as an initial template (these peptides are collectively named CT 10 -21 ). Studies on peptide fragments of hCT have suggested that residues in this region could play an important role in the activity and aggregation behavior of the full-length peptide (35,36). It has been shown in particular that five residues corresponding to positions 15-19 of hCT (DFNKF) play an active role in oligomerisation and fibril formation by hCT in vitro (35), and Lys-18 and Phe-19 have been identified as key residues in both the bioactivity and self-assembly of hCT (36).…”
Section: Resultsmentioning
confidence: 99%
“…To test the ability to predict the effect of multiple amino acid substitutions on the aggregation rate of a polypeptide sequence, a series of short peptides were designed by using amino acids 10-21 of hCT as an initial template (these peptides are collectively named CT 10 -21 ). Studies on peptide fragments of hCT have suggested that residues in this region could play an important role in the activity and aggregation behavior of the full-length peptide (35,36). It has been shown in particular that five residues corresponding to positions 15-19 of hCT (DFNKF) play an active role in oligomerisation and fibril formation by hCT in vitro (35), and Lys-18 and Phe-19 have been identified as key residues in both the bioactivity and self-assembly of hCT (36).…”
Section: Resultsmentioning
confidence: 99%
“…For this, we used an in silico approach applying the Waltz software (23). We first tested the software on hCT and sCT wild-type sequences, which were recognized as fibril-forming and aggregation-resistant according to reported experimental findings (11 (38,39) and the C-terminal region previously suggested as the fibril core (22,39,40).…”
Section: Resultsmentioning
confidence: 99%
“…Cell Culture-Human breast cancer T 47D cells were cultured as described (20) in RPMI 1640 containing 10% heat inactivated fetal bovine serum, 1% streptomycin/penicillin, 0.1 M insulin, and 0.1 M hydrocortisone in 5% CO 2 and 310 K. The latter hormones were omitted from the medium when subculturing cells to be used 1-3 days later for the receptor binding assay. Subculturing was performed with trypsin/EDTA as described (41,42), and for the binding experiments cells were subcultured in 12-well dishes. Receptor binding experiments were performed when cells reached 90% confluence (1-3 days after subculture).…”
Section: Methodsmentioning
confidence: 99%
“…Receptor Binding Assay-The assay was performed according to established protocols (41)(42). Briefly, cells in the 12-well dishes were washed with NaCl/P i (1 ml) at room temperature, and then prewarmed (310 K) assay buffer (RPMI 1640 and 0.1% (w/v) bovine serum albumin) was added to the cells (950 l).…”
Section: Methodsmentioning
confidence: 99%